2017
DOI: 10.1007/s00125-017-4320-5
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic ketoacidosis and diabetes associated with antipsychotic exposure among a previously diabetes-naive population with schizophrenia: a nationwide nested case–control study

Abstract: Antipsychotic exposure was associated with DKA and type 2 diabetes in a previously diabetes-naive schizophrenia population. Antipsychotic-associated DKA is relevant not only for psychiatrists but also for other physicians who may manage and admit such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…Antipsychotics have partial 5HT 2c properties; full agonists have been shown to reduce insulin secretion in isolated islets in animal studies (48). Finally in vitro effects have suggested clozapine has a direct effect to inhibit glucose-dependent insulin release by β-cell membrane hyperpolarisation (50).…”
Section: Insulin Secretionmentioning
confidence: 99%
“…Antipsychotics have partial 5HT 2c properties; full agonists have been shown to reduce insulin secretion in isolated islets in animal studies (48). Finally in vitro effects have suggested clozapine has a direct effect to inhibit glucose-dependent insulin release by β-cell membrane hyperpolarisation (50).…”
Section: Insulin Secretionmentioning
confidence: 99%
“…This is in line with the evidence of a recent large-scale systematic review and meta-analysis [25] that found a prevalence of only 2.9% of T2D in antipsychotic-naïve patients and 11.3% in patients with severe mental illness medicated with SGAs, with the highest prevalence associated with clozapine and olanzapine. A recent nationwide Danish study also reported a significant relationship between exposure to SGAs and diabetic ketoacidosis, caused by insulin deficiency [40]. In another Danish cohort, olanzapine and aripiprazole were shown to increase the rate of T2D in patients with schizophrenia by almost two-fold, whereas clozapine increased the rate four-fold [41].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the metabolic effects of psychotropic medications, especially antipsychotics and mood stabilizers, have been of concern in deteriorating the metabolic profile of pediatric patients. In addition, treatments with antipsychotics and antidepressants have also been linked to an increased risk of diabetic ketoacidosis and hypoglycemia . In addition, the appetite change and gastrointestinal adverse effects induced by certain antidepressants and ADHD medication may be challenging for maintaining stable glycemic control.…”
Section: Discussionmentioning
confidence: 99%